Haemato-Biochemical Changes in Dogs Affected with Immune Mediated Haemolytic Anaemia Caused by Babesia gibsoni - Reddy, Soundarya Thollapalli Chandrashekara; Chandrashekhariah, Anil Kumar Malige; Appaiah, Kshama Manepanda; Murag, Shivaraj; Kumar, Keeramande Ramakrishna Anjan; Hanumantha, Pavithra Balekatte (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The present study was conducted in dogs (n=18) presented to small animal OPD, Department of Veterinary Medicine in Bangalore with  clinical signs of canine babesiosis. Eighteen dogs were primarily screened for Babesia gibsoni infection by blood smear examinations and  then confirmed by PCR. Further these dogs were subjected to saline agglutination test, spherocytosis in blood smear examination and  Coombs test for diagnosis of immune mediated haemolytic anaemia (IMHA). The variations in haematological and serum biochemical  analysis of dogs affected with IMHA caused by Babesia gibsoni were studied. Haematology revealed significant increase in TLC and a  significant decrease in mean TEC, Hb, PCV and platelet count. Biochemical analysis revealed significant increase in mean ALT, ALP, total  bilirubin, creatinine, BUN; significant decrease in mean albumin level and non-significant decrease in total protein with non-significant  elevation in globulin levels.
Keywords: Babesia gibsoni,; Coombs test; Immune mediated haemolytic anaemia (IMHA); Saline agglutination test,; Spherocytosis.